Optimale medikamentöse Therapie bei Patienten nach akutem Koronarsyndrom - Stähli, Barbara E.; Landmesser, Ulf (DMW - Deutsche Medizinische Wochenschrift, 2018)
Antithrombotic therapy and other secondary preventive measures such as lifestyle changes, lipid lowering and blood pressure control, along with coronary revascularization strategies, can markedly improve clinical outcomes in patients after an acute coronary syndrome. Current guideline-recommended secondary preventive measures in patients with a recent acute coronary syndrome event according to the European Society of Cardiology (ESC) are summarized in this review.
Keywords: Akutes Koronarsyndrom; ST-Hebungsinfarkt; Nicht-ST-Hebungsinfarkt; anti-thrombotische Medikation; Sekundärprävention